THE EFFECT OF JOGGING EXERCISE ON BODY COMPOSITION AND GLUCOSE - Fahmi, Muhammad; Siantoro, Gigih; Winanda, Farayhan; Wahyudin, Ahmad; Syahra, Revina; Rani, Faisya; Andini, Dinda; Elita, Nabila; Setya, Anggun (Journal of Sport and Exercise Science, 2023)
ABSTRACT: Increased body weight or obesity at the adolescent level is very worrying, this phenomenon also has a significant prevalence in the causes of non-communicable diseases such as heart disease, diabetes, asthma and other diseases. Obesity can occur due to high intake of foods containing fat and sugar which, if not burned or managed by the body, will cause health problems. This study aims to determine the effect of physical activity in the form of 30 minutes of jogging on reducing body composition and glucose. A total of 25 students with an average age of 18-20 years participated in this research. They will do 30 minutes of jogging exercise 4 times a week for 3 weeks. Descriptive tests, normality and difference tests using SPSS 16 were used to explain the research results. The results of this research are p < 0.05, then the data Body Mass Index (IMT), Body Fat, Visceral Fat, Bone Mass, Body Muscle, Physical Rating, Basal Metabolic Rate, and Body Water experienced changes before and after 3 weeks of exercise. These changes show that jogging is good for health. The conclusion of this research is that jogging for 12 times has a significant impact on several components of body composition. Lack of physical activity causes an increase in body composition indicators which has a serious impact on a person's physical health and fitness, jogging is one of the recommended alternatives for keeping the body healthy and fit.